Synthesis, Characterisation of C-Methoxy Phenyl Calix[4]resorcinaryl Octacinnamate and Their Antibacterial Activity (Journal of Scientific Research, 2025)
The issue of antibiotic resistance has become a serious problem in the medical world. This resistance leads to reduced effectiveness of treatment for microbial infections and increases treatment costs. To address this issue, the discovery of new, non-resistant antibiotics is necessary. The aim of this study was to synthesize and evaluate the antibacterial activity of the compound C-methoxy phenylcalix[4]resorcinaryl octacinnamate (CMPCROC). The synthesis of CMPCROC was carried out by esterifying C-methoxy phenyl calix[4]resorcinarene (CMPCR) with cinnamoyl chloride. The product was characterized using IR spectroscopy, ¹H-NMR, and MS. The antibacterial activity was tested using the Kirby-Bauer disc diffusion method with amoxicillin as the positive control and water as the negative control. The synthesized compound was a yellow solid with a melting point of 215–220 °C and a yield of 67.05 %. The antibacterial test results showed that the inhibition zone of CMPCROC against Escherichia coli at a concentration of 50 ppm was 12.40 mm, while the positive control had a diameter of 15.30 mm. The inhibition zone of CMPCROC against Staphylococcus aureus was 11.63 mm, compared to 14.50 mm for the positive control. These results indicate that CMPCROC has strong antibacterial activity against E. coli and S. aureus and has potential for development as a new antibiotic in the future.